The Influence of Xanthan Gum and Lemon Juice on the Quality of Tomato Sorbet - Putri Ramadhany; Gerry Irawan (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2022)
Sorbet is one of common frozen desserts. It is prepared with low concentration of fat and protein; thus, the use of stabilizer in sorbet formulation extremely dictates the final properties. This current work investigated the quality (hardness, total solids, °Brix, viscosity, overrun, melting rate, vitamin C, lycopene content, and organoleptic test) of tomato-based sorbet added with different levels of xanthan gum as the stabilizer and lemon juice as the taste improver. The results showed that increase in xanthan gum level up to 0.5% was able to improve the overrun, melting rate, and lycopene content, i.e. 35%, 0.84 g/min, and 1.66 mg/100 g, respectively. Meanwhile, the addition of lemon juice into sorbet formulation could increase the content of vitamin C. Furthermore, addition of lemon juice was effective in removing the unpleasant tomato taste in the sorbet, but it did not affect the hardness, total solids, °Brix, lycopene content, viscosity, overrun, and melting rate.